Foreign lexical items in the lexicon of the Karaim language - Foltýn, Matyáš (Yearbook of the Poznan Linguistic Meeting, 2025)
The focus of this article is on a comprehensive etymological lexical analysis of the Karaim language as a whole and its dialects. While the practice of at least partially examining entire foreign elements within a specific language is relatively common nowadays (cf. Haspelmath & Tadmor 2009), Karaim has so far avoided this kind of comprehensive research with the literature focused around Zajączkowski (1959, 1961) and Jankowski (2013, 2015) providing papers focused either on diachronic development of specific loanwords or a basic general overview of the situation. The article, despite presenting only preliminary results of the analysis, aims to provide a more in-depth examination of the historical development and synchronic composition of the Karaim lexicon. The results indicate a pattern of distribution of loanwords among semantic classes seen in other languages, confirm the expected distribution of borrowings among semantic fields, clearly point out the lexical differences between West and East Karaim, and also show that the composition follows a pattern concerning the adoption of Hebrew and Slavic loanwords similar to that observable in the lexicon of Yiddish (Foltýn 2022). Despite the preliminary character of the results, they offer direct insight into the inner workings of the language’s lexicon.